Airborne Electromagnetic Signatures of an Ancient River in the Water‐Stressed Ganga Plain, Prayagraj, India: A Potential Groundwater Repository. Issue 23 (8th December 2021) - Chandra, Subash; Tiwari, Virendra M.; Vidyasagar, Mulavada; Raju, Kattula B.; Choudhury, Joy; Lohithkumar, K.; Nagaiah, Erugu; Chandrapuri, Sateesh; Ahmed, Shakeel; Verma, Saurabh K.
Abstract: The rapid depletion and deterioration of groundwater in the Ganga River Basin requires an effective water management plan for sustained water availability. An airborne electromagnetic study in the Ganga‐Yamuna doab, India, supplemented with drilling and logging data to address the groundwater crisis, has unraveled exhaustive aquifer information with a discovery of 45 km long buried river, having dimensions comparable to those of Ganga and Yamuna. This ancient river, likely to be extending toward the Himalaya, is characterized by a porous and permeable structures and is hydrogeologically linked with Ganga and Yamuna rivers through an underlying principal aquifer, which might hold a great promise for management of the current declining groundwater resources in the region. Interestingly, the location of this major paleoriver falls within the region where a lost mythological river was believed to be flowing in the past. The results add a new physical dimension to this belief. Plain Language Summary: 3D structural mapping of the relict signatures of the past imprint, specially meandering channels buried under soil cover in the current landscape and its linkages with other hydrogeological features that influence the hydrodynamic process, is science question of the utmost importance and practical relevance, particularly to address the fast depleting and deteriorating groundwater resources. The classical method of sediment coring, though capable for high‐resolution characteristics, but an expensive process and limited to small scale and hence may not be practical at regional scale. We use an airborne electromagnetic study that has unravelled exhaustive aquifer information with discovery of a buried paleoriver, having dimensions comparable to those of Ganga and Yamuna Rivers near Prayagraj, India. This ancient river, is characterized by a porous and permeable structure and is hydrogeologically linked with Ganga and Yamuna rivers through an underlying principal aquifer. Significantly, the location of this major paleoriver falls within the region where the lost River Saraswati was flowing in the past. The results add a new physical dimension to this mythological belief. Key Points: A comprehensive 3D map of aquifer system of the Ganga‐Yamuna doab, India Discovery of a 45 km long buried river with dimensions comparable to those of Ganga and Yamuna rivers, near Prayagraj, India These findings offer a new possibility for management of the dwindling groundwater in the Ganga‐Yamuna doab